Essential oil-containing solutions (mouthwashes) preserve dental enamel with releasing low Ca and P concentrations without morphology alterations: an in vitro study - Mutran, Sheila Cristina Almeida Neves; Carvalho-Filho, Paulo Roberto de; Ribeiro, Mara Eliane Soares; Faial, Kelson do Carmo Freitas; Lima, Rafael Rodrigues; D’Almeida Couto, Roberta Souza (Frontiers in Chemistry, 2024)
Introduction: The use of natural products such as essential oils has been suggested due to their promising pharmacological effects and economic viability. This study aimed to determine hydrogenic potential (pH), titratable acidity (TA), and ion concentrations of five solutions containing essential oils (EO), when used as a EO-containing solutions, and evaluate ion concentrations, enamel surface loss, and morphology alterations in enamel. Materials and methods: The pH, TA, calcium (Ca), potassium (K), and sodium (Na) concentrations of five EO-containing solutions were measured. Bovine enamel specimens were submitted to two daily 30-s immersions in artificial saliva, citric acid, distilled water, BaCloTea (Basil, Clove e Tea Tree), GeLaTeaPep (Geranium, Lavender, Tea Tree and Peppermint), EucaLem (Eucalyptus and Lemon), Cinnamon, or Spearmint solutions for 14 days. Ca, K, Na, and phosphorus (P) were quantified through ions chromatography, enamel surface loss was determined by profilometry, and surface morphology was qualitatively analyzed through scanning electron microscopy. Data were submitted to one-way ANOVA and Tukey (p < 0.05). Results: The five EO-containing solutions presented significantly lower pH values than distilled water (p < 0.05). The GeLaTeaPep group presented a significantly higher TA value than BaCloTea (p < 0.05), which in turn showed a significantly higher TA value than the other solutions (p < 0.05). The distilled water presented significantly higher Ca, K, and Na concentrations than all EO-containing solutions (p < 0.05). The enamel exposed to EO-containing solutions showed lower Ca and P concentrations than artificial saliva (control) as well as significantly higher surface loss; however, the surface morphology was similar to the artificial saliva. Conclusion: EO-containing solutions have low pH, TA, and low concentrations of Ca, Na, and K. Moreover, enamel exposed to these solutions showed low Ca and P concentrations and slight surface loss without morphology alteration.